Genetic Diversity among Local Quail Using RAPD-DNA Marker. / Diversidad Genética Entre Codornices Locales Usando Marcadores Dna-Rapd - Salahaldin Ahmed, Lajan; Salih AL-Barzinji, Yousif Mohamed (Revista Científica de la Facultad de Ciencias Veterinarias, 2020)
ABSTRACT The randomly amplified polymorphic DNA (RAPD) markers were used to detect the genetic variations and polymorphism among three different colors of local quail (desert, brown and white). Out of twenty random primers used, thirteen were able to amplify and showed bands. The total fragment number arrived 310 with size range from 250 to 2800 bp. Polymorphic fragments and unique bands in all samples were (34.36 and 2), respectively. However, OPA-04, OPS-01, OPB-01 and 10- MER loci have generated high polymorphic bands. The Nei’s gene diversity for overall lines averaged 0.1026.The higher distance found among brown female with both white and desert female (27.614), while the lowest distance (4.002) recorded between white and desert (male and female) quails. The overall dendrograms clustered the quail lines into two clusters. The 1st one consisted of white and desert, and the 2nd one included only brown. It was concluded that the white was closer to desert quail than to the brown quail.RESUMEN Los marcadores de ADN polimórfico amplificados al azar (RAPD) se utilizaron para detectar las variaciones genéticas y el polimorfismo entre tres colores diferentes de codornices locales (desierto, marrón y blanco). De los veinte cebadores aleatorios utilizados, trece pudieron amplificar y mostraron bandas. El número total de fragmentos llegó a 310 con un rango de tamaño de 250 a 2800 pb. Los fragmentos polimórficos y las bandas únicas en todas las muestras fueron (34,36 y 2), respectivamente. Sin embargo, los loci OPA-04, OPS-01, OPB-01 y 10-MER han generado altas bandas polimórficas. La distancia más alta se encontró entre las hembras marrones con hembras tanto, blancas como desérticas (27,614), mientras que la distancia más baja (4,002) se registró entre las codornices blancas y desérticas (machos y hembras). Los dendrogramas globales agruparon las líneas de codorniz en dos grupos. El primero consistía en blanco y desierto, y el segundo solo incluía marrón. Se concluyó que el blanco estaba más cerca de las codornices del desierto, que de las codornices marrones.